Characteristics and monetary compensation of caregivers for patients with rheumatic conditions (2019)
Musculoskeletal disorders (MD) are highly prevalent conditions that affect quality of life. MD cause physical and psychological dependence. Usually, the care of a patient with MD is assumed by a caregiver. The aim of this study was to describe the sociodemographic characteristics and the monetary remuneration associated to the care of a patient with MD. A cross sectional study was carried out in order to estimate the monetary remuneration related to the health care of patients with MD. A survey was applied to caregivers of patients with MD. Demographic data was collected. We asked about the relationship with the patient, the time as a caregiver and all data related to the monetary compensation. Descriptive epidemiology was done. We reported monetary data in American Dollars (USD) using the average exchange rate for 2018. We surveyed 132 caregivers. Mean age was 52 years [standard deviation 19], 72% were women, 78% were taking care of a patient with rheumatoid arthritis, 12% osteoarthrosis 2% lupus, and 2% osteoporosis. The remaining 6% were caregivers of patients with ankylosing spondylitis, fibromyalgia and Sjogren syndrome. Regarding the time as a caregiver, 48% had less than a year, 16% between two and three years, 18% more than three years, 13% more than four years, and 5% were temporarily caregivers. In our study, 85% of caregivers were a family member, while 15% a nurse or a non-related person. Regarding the compensation, 97% did not receive any salary or payment for being caregiver, the remaining 3% received between 265 and 530 USD per month. Our study demonstrated that the care for patients with MD is mainly assumed by family members. Our results agree with other studies in chronic conditions where only a small proportion of caregivers is paid. Caregivers should be considered for the health system.